The characteristics of the families of physically abused children - Robertson, Brian Aidan (Department of Psychiatry and Mental Health, 2018)
The study sets out to test the hypothesis that the families of physically abused children will show significant differences regarding their psychological, psychiatric and psychosocial characteristics when compared to families who do not have an abused child. The Index group was formed from 49 physically abused Coloured children and their families who were referred to the Red Cross War Memorial Children's Hospital in 1977. The ages of the children ranged from 5 months to 13 years, and 4 died as a result of their injuries. The Control group comprised 24 Coloured children (and their families) who were attending the hospital as outpatients over the same time period, and who were ill enough to be kept for overnight observation in the Emergency Ward. The two groups were matched for social class, age of the child and the marital status of the mother. The Index child was examined by a Paediatrician, and medical investigations requested when indicated. The following schedules were completed during the course of structured interviews with both groups of parents: The Circumstances of Injury/Illness Schedule, The Childrearing Attitudes Schedule and the Psychiatric Interview Schedule (which included a mental state examination). The Psychosocial Interview Schedule and an abbreviated IQ test were administered to the mothers only. The major significant finding of the study was the presence of abnormal personality functioning and psychiatric disorders of parents in nearly all the Index families. The type of psychiatric disorder was characteristically a neurosis in the mothers and personality disorders with alcohol and drug abuse, and criminality, in the fathers. The manifestations of the abnormal personalities of the Index parents included the use of regular physical punishment by the Index mothers, the repetitive physical abuse not only of the Index child but also of his siblings, and physical violence towards adults, especially of the Index fathers towards the Index mothers; the premarital conception of the Index child, the numbers of children of both Index parents by previous liaisons, and the lack of family cohesiveness of the Index parents; the loneliness of the Index mothers and their poor self-esteem; the financial debts of the Index families; and marital dysharmony. The Index families appeared to be of substantially lower social class than the general Coloured population of Cape Town. The following characteristics appeared to be associated with their low social class: low income, poor housing, unemployment, illegitimacy, teenage pregnancies, poor educational achievement and low IQ. Because of the matching for social class these characteristics were found to occur as commonly in the Control group. It was concluded that a combination of abnormal personalities and psychiatric disorders in the parents, factors associated with low social class, and marital dysfunction was the main etiological mechanism in the physical abuse of the Index children. The present study confirmed the finding of others that what distinguishes abusive parents from non-abusive parents is not so much the presence of specific abnormal childrearing practices or disturbances in particular parent-child relationships as the presence of a general disturbance of personality functioning and mental health. In other words, child abuse is only one of many deviant kinds of behaviour manifested by the parents of multi-problem families.